Explorations Between the Barents Sea and the Bering Strait: Reporting on the Pursuit of the Northeast Passage. (3rd April 2018) - Demhardt, Imre Josef
ABSTRACT: The cartographic unveiling of the Northeast Passage was a continuous and cosmopolitan process from the 1820s (Novaya Zemlya) to the 1910s (Severnaya Zemlya). Milestones including the ship expeditions Tegetthoff, Vega, and Jeannette are discussed from the angle of contemporary coverage in German geography journals.